Complete chloroplast genomes of Achnatherum inebrians and comparative analyses with related species from Poaceae. Issue 6 (10th May 2021) - Wei, Xuekai; Li, Xiuzhang; Chen, Taixiang; Chen, Zhenjiang; Jin, Yuanyuan; Malik, Kamran; Li, Chunjie
Abstract : This article reports the complete chloroplast genome of Achnatherum inebrians, a poisonous herb that is widely distributed in the rangelands of Northern China. The genome is 137 714 bp in total and consists of a large single‐copy (81 758 bp) region and small single‐copy (12 682 bp) region separated by a pair of inverted repeats (21 637 bp). The genome contains 130 genes, including 84 protein‐coding genes, 38 tRNA genes and 8 ribosomal RNA genes, and the guanine + cytosine content is 36.17%. We subsequently performed comparative analysis of complete genomes from A . inebrians and other Poaceae‐related species from GenBank. Thirty‐eight simple sequence repeats were identified, further demonstrating rapid evolution in Poaceae. Finally, the phylogenetic trees of 37 species of Poaceae and 2 species of Amaranthaceae were constructed by using maximum likelihood and Bayesian inference methods, based on the genes of the complete chloroplast genome. We identified hotspots that can be used as molecular markers and barcodes for phylogenetic analysis, as well as for species identification. Phylogenetic analysis indicated that A. inebrians is a member of the genus Stipa rather than Achnatherum . Abstract : The complete genomes from Achnatherum inebrians and other Poaceae‐related species from GenBank were subjected to comparative analysis. We not only identified hotspots that can be used as molecular markers and barcodes for phylogenetic analysis and species identification but also identified phylogenetic evidence that A. inebrians is a member of the genus Stipa sp. rather than Achnatherum sp. ​